Research Methods of Mathematics Teaching Methodology - Òtaganova Umida Egamberdi qizi (Journal of Higher Education and Academic Advancement, 2024)
In our country, teaching mathematics in elementary grades is generally considered as the first stage of mastering the school mathematics course.